Cigarette Smoke-Induced Reactive Oxygen Species Formation: A Concise Review - Yoon-Seok Seo; Jung-Min Park; Jae-Hyeong Kim; Moo-Yeol Lee (MDPI AG, 2023)
Smoking is recognized as a significant risk factor for numerous disorders, including cardiovascular diseases, respiratory conditions, and various forms of cancer. While the exact pathogenic mechanisms continue to be explored, the induction of oxidative stress via the production of excess reactive oxygen species (ROS) is widely accepted as a primary molecular event that predisposes individuals to these smoking-related ailments. This review focused on how cigarette smoke (CS) promotes ROS formation rather than the pathophysiological repercussions of ROS and oxidative stress. A comprehensive analysis of existing studies revealed the following key ways through which CS imposes ROS burden on biological systems: (1) ROS, as well as radicals, are intrinsically present in CS, (2) CS constituents generate ROS through chemical reactions with biomolecules, (3) CS stimulates cellular ROS sources to enhance production, and (4) CS disrupts the antioxidant system, aggravating the ROS generation and its functions. While the evidence supporting these mechanisms is chiefly based on in vitro and animal studies, the direct clinical relevance remains to be fully elucidated. Nevertheless, this understanding is fundamental for deciphering molecular events leading to oxidative stress and for developing intervention strategies to counter CS-induced oxidative stress.